The Influence of Sports Modern Dance on the Psychological Health of College Students - Jing Tang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim aimed to conduct a research on the impact of modern sports dance on college students' mental health. This study selected 200 non-sports major students from a school in a certain province that did not offer sports dance as the research subjects. Secondly, 100 students were randomly selected from another college in the province to take sports dance courses as an experimental group for a three-month study and training of sports dance courses. Randomly select 100 people from schools that have never offered sports dance as a control group, the control group did not take sports dance courses, but only underwent routine learning and exercise. The experimental period was three months, and the experimental group and the control group were measured with two mental health self-assessment scales before and after the experiment, after statistical analysis, the conclusion was drawn as follows: (1) Sports dance has a promoting effect on the mental health level of college students. (2) Sports dance can improve the physiological condition of college students. (3) Sports dance can improve the interpersonal skills of college students. (4) Sports dance can effectively resist the psychological barriers of college students. Sports dance is a very beneficial physical activity for the mental health of college students, by conducting sports dance teaching, students' social communication ability can be improved, self-confidence can be cultivated, and psychological problems can be prevented. Sports dance teaching, from a subconscious level, increases students' ability to withstand stress and is an effective way to improve their mental health level. This study could also helped to educational institutions to give importance on sports modern dance to increase psychological health of students.